1994
DOI: 10.1159/000112125
|View full text |Cite
|
Sign up to set email alerts
|

Transient Rise of Glucose Uptake in the Fetal Rat Brain after Brief Episodes of Intrauterine Ischemia

Abstract: In a rat model of intrauterine growth retardation and fetal brain ischemia, the maternal-fetal circulation was obstructed for up to 40 min in 20-day gestational age rats by occluding (restriction) the uterine blood vessels supplying the placenta. After restriction, flow was returned (reperfusion) for designated times. A time-dependent depletion of cerebral pyruvate levels (from 0.2 ± 0.02 to 0.06 ± 0.01 pmol/g wet weight) accompanied by an elevation in lactate concentration (from 1.95 ± 0.03 to 7.00 ± 0.56 umo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
(29 reference statements)
0
3
1
Order By: Relevance
“…An ADP/ATP ratio of 0.34 was calculated which appeared to be a little higher than expected for a normal high energy charge. In a previous study we also detected somewhat lower absolute ATP concentrations (Kunievsky et al, 1994) than those reported by Vannucci and Duffy (1976) for the fetal brain. The ADP/ATP ratio in the fetal liver was 0.49 in the control samples and as expected no PCr was detected (Fig.…”
Section: The Metabolic Fate Of 13 C-labeled Compounds After Ischemiacontrasting
confidence: 42%
See 2 more Smart Citations
“…An ADP/ATP ratio of 0.34 was calculated which appeared to be a little higher than expected for a normal high energy charge. In a previous study we also detected somewhat lower absolute ATP concentrations (Kunievsky et al, 1994) than those reported by Vannucci and Duffy (1976) for the fetal brain. The ADP/ATP ratio in the fetal liver was 0.49 in the control samples and as expected no PCr was detected (Fig.…”
Section: The Metabolic Fate Of 13 C-labeled Compounds After Ischemiacontrasting
confidence: 42%
“…In this particular set of experiments [1-13 C]glucose was injected at the end of the 20 min maternal fetal blood occlusion, just before circulation was restored. Under these conditions, the energy status as indicated by the levels of phosphocreatine, ATP, pyruvate and lactate was not significantly different between 15 min and 20 min restriction (Kunievsky et al, 1994). The flux of the 13 C label reflects therefore glucose metabolism during the reperfusion period.…”
Section: Metabolic Fate Of [1-13 C]glucose After Intraperitoneal Injementioning
confidence: 81%
See 1 more Smart Citation
“…18,19 The fetal brain has been reported to rely on anaerobic glycolysis to meet its energy demands. 20 Thus, GLUT is considered essential in the early organogenesis period. GLUT1, a major subtype of GLUT in fetal tissue, has been shown to mediate organogenesis in rat embryos.…”
Section: Introductionmentioning
confidence: 99%